PENGARUH CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT. KERETA API (PERSERO) BANDUNG (Suatu Survei Pada Konsumen Pengguna Kereta Api Argo Lawu Bandung – Surabaya di Stasiun Bandung) The Influence of Corporate Image To Consumer Purchasing Decision At PT. Kereta Api (Persero) Bandung (A Survey on Consumer Users Argo lawu Train Bandung – Surabaya Bandung Station) - Darmazakti Natajaya Tirtamahya (JURISMA : Jurnal Riset Bisnis & Manajemen, 2014)
The image is one of the most important asset of the company or organization should be established and maintained continuously. A good image is a powerful tool, not only to attract consumers in choosing products or companies, but also can improve the attitudes and customer satisfaction to the company. Meanwhile, consumer purchasing decisions as an individual process of selecting, organizing, and interpreting the input information to create a meaningful picture of the world. The purpose of this research is to know company image at. Kereta Api (Persero) Bandung, and examine the influence of corporate image on consumer purchasing decisions at. Kereta Api (Persero) Bandung Research developed by using and survey method. This research also using descriptive and verifikatif  methods. Population 850 consumer, and the technique of sample this reseach which using a acccidental sampling with the result that for obtainabl 90 consumer as sample. Technique in collecting data by use of interview, observation, questioners and documentation. The analyze method by use of a correlation of product moment, and coefficient of determination, as well as test of t with by use of help SPSS 13.0 for windows. Results of research on the influence of corporate image shows quite good results, as well as with consumer purchasing decisions showing good results. Results of analysis showed the influence of corporate image on consumer purchasing decisions at. Kereta Api (Persero) Bandung indicates a strong degree of correlation with the contribution of influence as much as 60.84%, and the rest as much 39.16% influenced by other factors which not analyzed , namely initiator, influences, Devider, buyer,service and the price.  Keywords :  Corporate Image, Consumer Puchasing Decisions, at PT. Kereta Api (Persero) Bandung